MONITORING OF STUDENTS' INFORMATION COMPETENCE OF THE SPECIALITY 032001 − DOCUMENTATION MANAGEMENT AND ADMINISTRATIVE SUPPORT - Vyacheslav V. Persianov; Alexey V. Gordeyev (Открытое образование (Москва))
The article deals with the method of information competence development of Documentation management and administrative support students (specialty 032001). The method is approved in the educational environment of Tula state pedagogical university by L.N. Tolstoy and has proved its high effi ciency.